Amyand’s Hernia, State of the Art and New Points of View - Guido Mantovani; Michela De Angelis; Francesco Di Lecce; Annalisa Pascariello; Domenico Risio; Luigi Boccia (Case Reports in Surgery)
Background. Amyand’s hernia (AH) is an inguinal hernia containing the vermiform appendix, with an incidence between 0.4% and 1% of all inguinal hernias. Acute or perforated appendicitis can complicate AH. Case Presentation. A 75-year-old Caucasian man presented with incarceration of vermiform appendix in inguinal hernia sac. Diagnosis was posed preoperatively with computed tomography (CT) scan. Patient underwent urgent surgery and simultaneous appendectomy and hernia repair by Bassini’s technique were performed. Conclusions. Preoperative diagnosis of AH is rare; however it could be useful for surgeon to choose operative approach. Treatment of AH depends on grade of appendix inflammation and/or perforation. The technique utilized to repair hernia depends largely on surgeon’s preferences; the presence of inflamed or perforated appendix is not an absolute contraindication for using a prosthetic mesh.